2020
DOI: 10.1109/tsp.2020.2983833
|View full text |Cite
|
Sign up to set email alerts
|

Polyphase Waveform Design for MIMO Radar Space Time Adaptive Processing

Abstract: We consider the design of polyphase waveforms for ground moving target detection with airborne multiple-inputmultiple-output (MIMO) radar. Due to the constant-modulus and finite-alphabet constraint on the waveforms, the associated design problem is non-convex and in general NP-hard. To tackle this problem, we develop an efficient algorithm based on relaxation and cyclic optimization. Moreover, we exploit a reparameterization trick to avoid the significant computational burden and memory requirement brought abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 40 publications
(66 reference statements)
0
33
0
Order By: Relevance
“…where p is the radar transmitted waveform and M is the signal-independent disturbance covariance. Now, following the line of reasoning of some already published papers [25], [30], [33], [56], an iterative and alternating optimization approach is herein implemented. Precisely, at each step only one variable is optimized while the other is maintained fixed, and viceversa at the next step.…”
Section: F Joint Phase-only Stap and Transmitting Waveform Optimizationmentioning
confidence: 99%
“…where p is the radar transmitted waveform and M is the signal-independent disturbance covariance. Now, following the line of reasoning of some already published papers [25], [30], [33], [56], an iterative and alternating optimization approach is herein implemented. Precisely, at each step only one variable is optimized while the other is maintained fixed, and viceversa at the next step.…”
Section: F Joint Phase-only Stap and Transmitting Waveform Optimizationmentioning
confidence: 99%
“…Afterwards, the authors in [ 6 , 7 ] adopted a genetic algorithm and the Niche genetic algorithm in the optimization process to improve the orthogonality of the code sets. In [ 8 ], the authors revealed a problem that the method could be trapped in the local minimum shortly after initialization, which resulted in poor performance when designing a polyphase waveform. To solve this problem, the authors proposed a relaxation and cyclic optimization algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…We note that some prior work such as [25]- [27], [31] is developed based on the assumption that the spatial-temporal steering vectors u c,l,k of the clutter are known a priori, or in other words that the azimuths, ranges, and Doppler frequencies of the clutter patches are exactly known. In practice, however, it is difficult to obtain parameters such as these for the signaldependent clutter.…”
Section: A Radar Received Signal and Radar Performance Metricmentioning
confidence: 99%
“…It can be observed that with a fixed transmit waveform x, the original problem (26) becomes a well-known minimum variance distortionless response (MVDR) problem [27], [31]:…”
Section: Problem Formulationmentioning
confidence: 99%